2013
DOI: 10.4103/0973-6042.114225
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty in acute fractures of the proximal humerus: A systematic review

Abstract: The indications for surgical intervention in complex fractures of the proximal humerus are disputed. In elderly patients with poor bone stock it may be impossible to obtain satisfactory fixation of the tuberosities to a hemiarthroplasty (HA). In such cases primary insertion of a reverse shoulder arthroplasty (RSA) has been suggested. We aimed to review clinical studies reporting benefits and harms of RSA in acute fractures. A systematic review. We included 18 studies containing 430 RSA in acute fractures. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…There are several studies reporting the results of shoulder arthroplasty for the treatment of acute PHF [7,16,19,22,26,28,31], even comparing anatomic and RSA [6,8,13,24]. Essentially, in the acute scenario, shoulder arthroplasty has demonstrated improvements in pain, function, satisfaction and bone healing [6-8, 13, 16, 19, 22, 24, 26, 28, 31].…”
Section: Discussionmentioning
confidence: 98%
“…There are several studies reporting the results of shoulder arthroplasty for the treatment of acute PHF [7,16,19,22,26,28,31], even comparing anatomic and RSA [6,8,13,24]. Essentially, in the acute scenario, shoulder arthroplasty has demonstrated improvements in pain, function, satisfaction and bone healing [6-8, 13, 16, 19, 22, 24, 26, 28, 31].…”
Section: Discussionmentioning
confidence: 98%
“…Although recent studies reported satisfactory results with RSA, 15,20,23,35 they also reported a relevant number of complications. 6,9 Moreover, there were few studies comparing the 2 types of prostheses for these acute fractures. We have found only 4 retrospective comparative studies 5,16,17,36 and 1 other prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…Successful results with use of the superior approach for RSA have been shown in treatment of acute proximal humeral fractures in a recent systematic review. 7 The results of the systematic review did not show superiority of any specific approach for this indication. In scenarios in which the proximal humerus is fractured, achieving proper baseplate tilt is aided by the lack of intact proximal humeral bone that otherwise hinders correct positioning of the component.…”
Section: Surgical Approach: Anterosuperior Vs Deltopectoralmentioning
confidence: 92%
“…19 In addition, patients with proximal humerus fractures may be well treated with the AS approach. 7 The surgeon's experience with the particular approach is another critical factor, regardless of whether the AS or DP approach is chosen.…”
Section: Surgical Approach: Anterosuperior Vs Deltopectoralmentioning
confidence: 99%